Band structure of BeTe: A combined experimental and theoretical study - Nagelstraßer, M.; Dröge, H.; Steinrück, Hans-Peter; Fischer, F.; Litz, T.; Waag, Andreas; Landwehr, G.; Fleszar, A.; Hanke, W. (Physical Review B, 1998)
Using angle-resolved synchrotron-radiation photoemission spectroscopy we have determined the dispersion of the valence bands of BeTe(100) along ΓX, i.e., the [100] direction. The measurements are analyzed with the aid of a first-principles calculation of the BeTe bulk band structure as well as of the photoemission peaks as given by the momentum-conserving bulk transitions. Taking the calculated unoccupied bands as final states of the photoemission process, we obtain an excellent agreement between experimental and calculated spectra and a clear interpretation of almost all measured bands. In contrast, the free-electron approximation for the final states fails to describe the BeTe bulk band structure along ΓX properly.